Constructing Interpersonal Meaning via Teacher Talk in Chinese as a Second Language Classrooms: An Appraisal Analysis - Heng, Buai Chin; Taib, Fauziah; Cheong, Cecilia Yin Mei (Journal of Modern Languages, 2017)
This paper aims to examine how interpersonal meaning is constructed through the use of attitudinal resources in teacher talk in Chinese as a second language (CSL) classrooms in selected schools in Malaysia; from the perspective of the Appraisal framework proposed by Martin and White (2005). The focus is on how these resources help teachers to establish rapport with students of various races learning CSL; and thus facilitate learning of the target language, Mandarin. The corpus consists of four hours of recording and observation of four national primary schools in the state of Selangor that offer CSL classes. Analysis shows that attitudinal resources realise rapport through teachers’ acts of providing encouragement, giving positive feedback, facilitating face-saving and in promoting students’ self-esteem during classroom teaching. As not much research has been carried out on analysing attitudinal resources in teacher talk (Zhu, 2015), this study hopes to provide information on how teachers can utilise these resources in building rapport with students and thus enhance language learning in CSL classrooms in Malaysia.